COVID-19 Salgınının Sağlık Çalışanlarında İkincil Travmatik Strese ve Uyku Kalitesi Üzerine Etkisi. - DEMİRTÜRK SELÇUK, Ezgi; DEMİRBA, Birsel Canan (Turkiye Klinikleri Journal of Nursing Sciences, 2021)
Objective: The aim of this study is to examine the relationship between the coronavirus epidemic and secondary traumatic stress and sleep quality in healthcare workers. Material and Methods: The universe of this descriptive and cross-sectional study; in Turkey the primary care, health care workers who were working in secondary and tertiary health care services has joined. The snowball sampling method was used in the study, and healthcare workers who voluntarily accepted to participate in the study were included in the study. The data were collected using a personal information form, Secondary Traumatic Stress Scale, and Pittsburgh Sleep Quality Index (PSQI). Descriptive statistics of the data are given as frequency, percentage, mean, standard deviation, median, minimum, maximum. ANOVA, Kruskal-Wallis, Mann-Whitney U test and Spearman correlation analysis were used for statistical comparisons. The data obtained from the research were analyzed with SPSS (Statistical Package for Social Science) 22.0 statistics program. Results: Health workers participating in the study was 45.2% are 31-40 years old, 77.6% are women, 61.1% are undergraduate, 76.2% are nurses/midwives, 64.4% are married, 43.9% have no children, 65% are with their spouses and children live together. 39.6% of the healthcare professionals provided care to the patient who had a positive coronavirus disease-2019 (COVID-19) test, and 9.2% were diagnosed with COVID-19. It was determined that the PSQI total score mean of healthcare workers was 8.84±3.58. The secondary traumatic stress scale mean score of the employees in the study was found to be 45.01±15.51. Conclusion: The pandemic period causes psychological and physical disorders in healthcare workers. This study found that this group had high levels of insomnia and secondary traumatic stress. Considering that employees with this condition may make much more mistakes and experience burnout, it may be recommended to plan their working hours very carefully in line with the results of this study and to take care of COVID-19 patients with the circulation method.